Non Cirrhotic Portal Fibrosis - Ralph Girson; Andri Sanityoso; Rino A Gani; Wirasmi Marwoto; Murdani Abdullah; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Diagnosis of non cirrhotic portal fibrosis was considered when the following criteria were fulfilled evidence of portal hypertension (oesophageal varices, hypersplenism, ascites, or increased hepatic venous pressure gradient), Doppler ultrasound showing patent portal and hepatic veins, and liver biopsy showing sign of cirrhosis. Non cirrhotic portal fibrosis clinically characterized by splenomegaly, anemia, portal hypertension, and histopathological examination portal tract showing fibrosis and sclerosis. Portal hypertension are most caused by a cirrhotic liver (85%), there are only a few reports on non cirrhotic portal hypertension, mostly in Japan and India. We reported a case of non cirrhotic portal fibrosis in young male.  The clinical complications of portal hypertension are variceal bleeding and pancytopenia due to hypersplenism. Variceal band ligation and splenectomy were performed. The patient showed good clinical response.   Keywords: portal hypertension, non cirrhotic portal fibrosis, young male